STATISTICAL ANALYSIS OF THE RESULTS OF SYNCHRONIZATION OF THE CONTOURS OF AUTONOMIC CONTROL OF CARDIOVASCULAR SYSTEM DURING THE FUNCTIONAL TEST WITH BREATHING OF VARIABLE FREQUENCY - EI I Borovkova; EA A Manafova; AA A Zazulya; AS S Karavaev; AR R Kiselev (Наука и инновации в медицине, 2016)
Aim - the study of characteristics of the interaction between the contours of autonomic regulation of the cardiovascular system. Materials and methods. We studied the recordings of electrocardiograms and photoplethysmograms of 25 healthy subjects taken during the functional test with chirp breathing. Synchronization of the regulation contours was studied using the previously proposed approaches. Statistical analysis of the results was carried out. Results. We have studied the rhythms with a frequency of about 0.1 Hz. It was revealed that these rhythms are synchronized under the influence of breath. We calculated the duration of the synchronization intervals. Conclusion. The results support the hypothesis for autonomy and functional independence of the studied regulation contours.